The Impact of EU Regional Policy on Economic Growth, Promoting Access to Employment and Social Inclusion - Małgorzata GORZAŁCZYŃSKA-KOCZKODAJ (Communications of International Proceedings, 2020)
Regional development is largely an economic process, involving the transformation of regional factors and resources (internal and external) into goods and services. Its main feature is the growth of the region, i.e. the increase in the production of goods and services as a result of a quantitative increase in used factors of production (material and personal) and improvement of their efficiency. The aim of the article is to analyse the EU funds and determine the impact of EU funds received by Poland under the financial perspective 2007-2013 and 2014-2020 for reducing unemployment and for economic growth. The article shows the important role that the European Union plays in supporting employment through the implementation of the main objective of cohesion policy supporting employment, business competitiveness and economic growth and sustainable development, as well as improving the quality of life of citizens. The objectives of this policy are addressed to all regions and cities in the European Union. Detailed data cover different periods in the analysed range, due to their availability. The presented results form the basis for further, extensive research, in order to fully specify factors affecting the described phenomena and their role. Due to a limited space, many details as well as factors directly affecting the analysed phenomenon, such as changes in social policies in the country, are not taken into account.
Keywords: EU funds; GDP; Registered Unemployment; Relative Poverty